2008
DOI: 10.1111/j.1365-2966.2008.13983.x
|View full text |Cite
|
Sign up to set email alerts
|

Finding rare objects and building pure samples: probabilistic quasar classification from low-resolution Gaia spectra

Abstract: We develop and demonstrate a probabilistic method for classifying rare objects in surveys with the particular goal of building very pure samples. It works by modifying the output probabilities from a classifier so as to accommodate our expectation (priors) concerning the relative frequencies of different classes of objects. We demonstrate our method using the Discrete Source Classifier (DSC), a supervised classifier currently based on support vector machines, which we are developing in preparation for the Gaia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…For a more detailed description of SVMs and references, we refer to Paper I, while a more general aspect of the Gaia classification scheme can be found in Bailer-Jones et al (2008). Throughout this section, we consider truncated spectra, retaining only 77 of the 96 data points of the simulated BP and RP spectra corresponding to the wavelength range 321.43-998.02 nm and 613.78-1130.25 nm for the two photometers, respectively.…”
Section: Classification and Parametrizationmentioning
confidence: 99%
“…For a more detailed description of SVMs and references, we refer to Paper I, while a more general aspect of the Gaia classification scheme can be found in Bailer-Jones et al (2008). Throughout this section, we consider truncated spectra, retaining only 77 of the 96 data points of the simulated BP and RP spectra corresponding to the wavelength range 321.43-998.02 nm and 613.78-1130.25 nm for the two photometers, respectively.…”
Section: Classification and Parametrizationmentioning
confidence: 99%
“…Carricajo et al 2004) etc. It is noted that Bailer-Jones et al (2008) and Saglia et al (2012) reported the applications of the support vector machine (SVM) in the star-galaxy-QSO classifications. In general, this new technique can also be used for the classification of stars.…”
Section: Introductionmentioning
confidence: 99%
“…From this analysis it follows that the calibration errors influence only bright objects (V < ∼ 16 mag), samples with low S/N remain almost unchanged. Scaling the S/N to fainter objects, we conclude that the main noise contribution for quasar spectra is Poisson noise from the source (Bailer-Jones et al 2008). From this, we can estimate that the S/N is proportional to the square root of the source flux.…”
Section: Simulating Gaia's Low-resolution Spectra Of Quasarsmentioning
confidence: 81%